Artificial Intelligence, Social Media, and Modern Teenagers - Hikmawati, Hanifah; Darma, Mega Putri Aulia (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
AI is known as artificial intelligence as a computer system-based technology that has the ability to carry out human activities. Its reliable intelligence in storing data or